INNOVATION OF ISLAMIC BOARDING SCHOOL-BASED CURRICULUM MANAGEMENT - Mubarok, Sofil; Furqan, Moh; Maulana, Muhammad Zaki (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the process of forming a generation with a deep understanding of Islamic teachings through the application of a modern approach. MA Nurul Qur'an has succeeded in combining Islamic traditions with innovative learning methods, enabling students to better understand religious values contextually and relevant to today's times. By utilizing technology, interactive learning methods, and the latest curriculum development, MA Nurul Qur'an creates a dynamic and inspiring learning environment. This research uses a descriptive qualitative research approach. Case study at MA Nurul Qur'an Kraksaan Probolinggo. This research uses a qualitative case study type method by conducting research aimed at describing problems and analyzing the problems that occur. Researchers collected data through several stages such as; observation, observing directly at the research site. Interview, interviewing a number of informants at the research location. Observation, visiting research locations. Documentation study, analyzing documents related to research. The research results show that by implementing progressive learning methods and supporting technology, MA Nurul Qur'an has succeeded in creating a learning environment that is dynamic and relevant to the needs of the times. This article also explores the implementation of current curricula and the use of multimedia resources in the teaching process. It is hoped that the innovative approach implemented by MA Nurul Qur'an can provide inspiration and guidance for other Islamic religious education institutions in increasing the effectiveness of learning, so that they can form a generation that has a deep and applicable understanding of Islamic values in a modern context.